High-dimensional intravital microscopy reveals major changes in splenic immune system during postnatal development - Porto-Pedrosa, Maria Luiza Mundim; de Miranda, Camila Dutra Moreira; Lopes, Mateus Eustáquio; Nakagaki, Brenda Naemi; Mafra, Kassiana; de Paula, Cristina Maria Pinto; Diniz, Ariane Barros; Costa, Karen Marques de Oliveira; Antunes, Maisa Mota; Oliveira, André Gustavo; Balderas, Robert; Lopes, Rodrigo Pestana; et al. (Frontiers in Immunology, 2022)
Spleen is a key organ for immunologic surveillance, acting as a firewall for antigens and parasites that spread through the blood. However, how spleen leukocytes evolve across the developmental phase, and how they spatially organize and interact in vivo is still poorly understood. Using a novel combination of selected antibodies and fluorophores to image in vivo the spleen immune environment, we described for the first time the dynamics of immune development across de postnatal period. Also, we revealed how infections – using a model of malaria - can change the spleen immune profile in adults and infants, which could become the key to understanding different severity grades of infection. Our new imaging solutions can be extremely useful for different groups in all areas of biological investigation, paving a way for new intravital approaches and advances.